Tafsir Kontekstual Surah Al-Maidah 49-50 Sebagai Anti Tesis Terhadap Ideologi Fundamentalis Di Indonesia: Pendekatan Kontekstual Abdullah Saeed - Fatmawati, Fatimah (Institut Agama Islam Negeri Fattahul Muluk Papua, 2022)
This study aims to analyze the meaning of Hukmullah (God's law) in the QS. Al-Maidah 49-50. This study is important considering the many efforts made by Islamic-Fundamentalist group to clash Pancasila’s law with God's law. This research answers two question: First, what is the meaning of God’s law and jahiliyyah’s law in the QS. Al-Maidah 49-50. And Second, how is the relevance of QS. Al-Maidah 49-50 with the current law in Indonesia. To answer this question, Abdullah Saeed's Contextual Tafsir is used. The result is that the Jahiliyyah law refers to discriminatory law based on lust and social status, while Allah's law refers to justice and egalitarianism. Thus, by using Abdullah Saeed's term, the verse has an instructional value, with universal message. It is not a specific command that obliges formal Islamic Law in the state system. In the current era, the existing law in Indonesia has been based on the principle of justice. This principle of justice is one of the points in the ideology agreed upon since the beginning of the founding of the Indonesian nation, namely Pancasila. The precepts is: Social Justice For All Indonesian People. This research is limited to the meaning of hukmullah in QS. Al-Maidah 49-50, so that this research can be developed further to find the meaning of hukmullah in other surah in the al-Qur’an.